2021
DOI: 10.1038/s41598-021-86346-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremic sepsis leads to higher mortality when adjusting for confounders with propensity score matching

Abstract: One can falsely assume that it is well known that bacteremia is associated with higher mortality in sepsis. Only a handful of studies specifically focus on the comparison of culture-negative and culture-positive sepsis with different conclusions depending on study design. The aim of this study was to describe outcome for critically ill patients with either culture-positive or -negative sepsis in a clinical review. We also aimed to identify subphenotypes of sepsis with culture status included as candidate clini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Furthermore, the prevalence of culture positive sepsis reported from several ICU in South Asia ranged from 6 to 56%, 52.9% in this study was near comparable with the study by Lisa Mellhammar et al 18 having 54%, most likely is due to discrepancies in study design and terminology. 12, [14][15][16][17][18] In our study culture positivity was 52.9% among elevated CRP Patients similar to the study of Jyoti et al study who also got 49% with CRP elevated above 6mg/dl 12 n a study done by Abera Kumalo culture positivity was a 16% & even low as near 7% in recent study by Bajaj A et al 19 in may be because they did not take CRP positivity as adjunct criteria for selecting samples. 20 In our study, major positive samples were from IMCU (42.6%) similarly higher percentages are seen in other studies also, a study done by Calik Z had highest percentage with 81% of his samples were from IMCU.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the prevalence of culture positive sepsis reported from several ICU in South Asia ranged from 6 to 56%, 52.9% in this study was near comparable with the study by Lisa Mellhammar et al 18 having 54%, most likely is due to discrepancies in study design and terminology. 12, [14][15][16][17][18] In our study culture positivity was 52.9% among elevated CRP Patients similar to the study of Jyoti et al study who also got 49% with CRP elevated above 6mg/dl 12 n a study done by Abera Kumalo culture positivity was a 16% & even low as near 7% in recent study by Bajaj A et al 19 in may be because they did not take CRP positivity as adjunct criteria for selecting samples. 20 In our study, major positive samples were from IMCU (42.6%) similarly higher percentages are seen in other studies also, a study done by Calik Z had highest percentage with 81% of his samples were from IMCU.…”
Section: Discussionsupporting
confidence: 82%
“…21 Gram negative bacteria 33 (61.1%) organisms were isolated more compared to Gram positive cocci 17 (31.5%) in our study. Similarly GNB was most commonly isolated organisms in many studies evident in Bajaj et al 18 from southern India region (65%) & from northern India one study done by Surbhikhurana et al, a 4 years study showed a percentage variations from 78% to 85%. This is well known as Gram-negative bacilli produces endotoxins that kick start the septicemia.…”
Section: Discussionmentioning
confidence: 86%
“…Pathogenemia refers to an infective agent measurable in the blood. For patients with sepsis, pathogenemia is associated with worse outcomes [ 15 , 16 ]. Furthermore, the pathogen load is directly linked to higher morbidity and mortality [ 17 19 ].…”
Section: Pathogenesis Of Sepsismentioning
confidence: 99%
“…10 A recent study found that, among critically ill adults who met Sepsis-3 diagnostic criteria, those with bacteremia had proportionally higher mortality compared with those without bacteremia. 32 This finding may partially explain the relatively lower mortality observed with the automated clinical method compared with the NTDB because the automated clinical method incorporates cultures from different body tissues. Although the NTDB and the automated clinical method had similarly strong associations with chronic critical illness, only a few patients at high risk were identified by the NTDB.…”
Section: Discussionmentioning
confidence: 99%